Cover Picture: High Performance and Long‐cycle Life Rechargeable Aluminum Ion Battery: Recent Progress, Perspectives and Challenges (Chem. Rec. 12/2022). Issue 12 (12th December 2022) - Abu Nayem, S. M.; Ahmad, Aziz; Shaheen Shah, Syed; Saeed Alzahrani, Atif; Saleh Ahammad, A. J.; Aziz, Md. Abdul
Abstract : The Front Cover depicts the design concepts and efficiency outcome of a high‐performance, long‐cycle life and safe rechargeable aluminum ion battery with a low‐cost. See the Review by Md. Abdul Aziz, A. J. Saleh Ahammad and co‐workers (DOI: 10.1002/tcr.202200181 ).